Correction to: One decade of glioblastoma multiforme surgery in 342 elderly patients: What have we learned? (Journal of Neuro-Oncology) - Heiland, Dieter Henrik; Haaker, Gerrit; Watzlawick, Ralf; Delev, Daniel; Masalha, Waseem; Franco, Pamela; Machein, Marcia; Staszewski, Ori; Oelhke, Oliver; Nicolay, Nils Henrik; Schnell, Oliver (Journal of Neuro-Oncology, 2018)
Correction to: Journal of Neuro-Oncology https://doi.org/10.1007/s11060-018-2964-8 There was a typo in the third author’s name in the initial online publication. The original article has been corrected.
CRIS-Team Scopus Importer:2023-09-13